Status and Prospects of Integrated Pest Management in Apple Production in Hungary - Apáti, Ferenc (Acta Agraria Debreceniensis, 2005)
Farming methods supporting the ecological function of agriculture will play an even more dominant role in the near future than they do now, as much in Hungary as in the rest of the EU.Several farming techniques supporting sustainable development have already evolved, and in this essay, I deal with integrated production i.e. integrated fruit production in Hungary and its perspectives. I analyze both European and Hungarian regulations on integrated production and their development.It is obvious that in the orchards of Europe, integrated production is gaining ground. We can expect the increased spread of this western trend to Hungary, too, because one of the conditions for remaining on the market will be a product from integrated production. However, we cannot expect any rapid increase in the future. In my opinion, there are three ways to propagate integrated production:− changes in the approach of farmers;− vocational training of farmers because of the greater „knowledge-demand”; improving the consultant network;− strict monitoring of the production process.